Knowledge, Attitude and Practice of Healthcare Providers on the Management of Malaria Cases in the Province of Tshopo, Democratic Republic of the Congo - Olonga, Atike Rachel; Tagoto, Tepungipame Alliance; Basandja, Longembe Eugene; Boande, Losangola Gaston; Mokoto, Lokoni Veronique; Panda, Lukongo John; Meta, Kalala Annie; Mukadi, Kaningu Pierre; Mandoko, Nkoli Papy; Labama, Otuli Noel; et al. (International Journal of Health Sciences, 2024)
Purpose: The objective of this study was to determine knowledge, attitudes and practices relating to malaria, the control strategy (preventive and curative) and the circulation of antimalarials in order to establish a behavioral basis and their implications for the control of malaria, a scourge that is decimating our populations. Methodology: a cross-sectional study was conducted from August 24 to December 24, 2022 in the province of Tshopo in the DRC. The data for the present study were collected from 150 providers who voluntarily agreed to answer our questions in 4 malaria case management structures. Findings: more than half of the subject had knowledge of malaria, there was a statistically significant association with malaria treatment according to national guidelines p<0.001 and malaria resistance p<0.001. More than half of providers report their malaria cases and 1/3 do not report which showed a statistically significant association p<0.001 and not referring showed a statistically significant association p<0.001. Unique contribution to theory, practice and policy: Adherence to national guidelines remains a major challenge in the strategy to combat malaria in this part of the DRC. It is imperative to initiate formative supervision in case management structures and also awareness campaigns for adherence to national policy.